2019
DOI: 10.1097/aud.0000000000000780
|View full text |Cite
|
Sign up to set email alerts
|

10-Year Follow-Up Results of The Netherlands Longitudinal Study on Hearing: Trends of Longitudinal Change in Speech Recognition in Noise

Abstract: Objectives: Previous findings of longitudinal cohort studies indicate that acceleration in age-related hearing decline may occur. Five-year follow-up data of the Netherlands Longitudinal Study on Hearing (NL-SH) showed that around the age of 50 years, the decline in speech recognition in noise accelerates compared with the change in hearing in younger participants. Other longitudinal studies confirm an accelerated loss in speech recognition in noise but mostly use older age groups as a reference. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 50 publications
1
34
0
Order By: Relevance
“…In a previous study using the Netherlands Longitudinal Study on Hearing (NL-SH), we found that a history of tobacco smoking was related to an increased rate of decline in speech recognition in noise [Goderie et al, 2020]. The mechanism to explain this association is unclear, but it is hypothesized that atherosclerosis, the major cause of CVD, plays a role in the association [Makishima, 1978;Guo et al, 2005;Nomiya et al, 2008].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a previous study using the Netherlands Longitudinal Study on Hearing (NL-SH), we found that a history of tobacco smoking was related to an increased rate of decline in speech recognition in noise [Goderie et al, 2020]. The mechanism to explain this association is unclear, but it is hypothesized that atherosclerosis, the major cause of CVD, plays a role in the association [Makishima, 1978;Guo et al, 2005;Nomiya et al, 2008].…”
Section: Introductionmentioning
confidence: 97%
“…Age, sex, and history of smoking were included in the models as potential confounders or moderators. Each of these variables has been examined as single risk factors for hearing loss in a previous study using the NL-SH cohort [Goderie et al, 2020].…”
Section: Introductionmentioning
confidence: 99%
“…The NL-SH uses both the National Hearing Test (NHT) ( Smits et al 2006 ), and an extensive online questionnaire, which addresses hearing status, health, work, and health care use. More details about the study design and recruitment of participants can be found in earlier publications (e.g., Stam et al 2015 ; Goderie et al 2020 ). Data collection started from 2006 onward (T0).…”
Section: Methodsmentioning
confidence: 99%
“…Worldwide, approximately one-third (33%) of people aged 65 years and older suffer from disabling HI ( WHO 2017 ). However, hearing decline starts at a younger age and, on average, accelerates around the age of 50 years ( Dawes et al 2014 ; Goderie et al 2020 ). This indicates that HI affects many persons in the working population ( Kramer & Goverts 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Throughout life, hearing deteriorates as age increases, but many other risk factors may influence the development of hearing loss (Goderie et al 2020;Van Eyken, Van Camp, and Van Laer 2007). Several potential causes have been identified, including noise exposure, tobacco smoking, genetic factors, certain medical conditions, and certain medications (Besser et al 2018;Cianfrone et al 2011;Goderie et al 2020;Kiely et al 2012;Momi et al 2015). Toxicity to the ear, known as ototoxicity, is well established for certain medications, such as cisplatin and aminoglycosides (Ganesan et al 2018).…”
Section: Introductionmentioning
confidence: 99%